Peripheral modifications of [Ψ[CH(2)NH]Tpg(4)]vancomycin with added synergistic mechanisms of action provide durable and potent antibiotics - Okano, Akinori (Proc Natl Acad Sci U S A, 2017)
Subsequent to binding pocket modifications designed to provide dual d-Ala-d-Ala/d-Ala-d-Lac binding that directly overcome the molecular basis of vancomycin resistance, peripheral structural changes have been explored to improve antimicrobial potency and provide additional synergistic mechanisms of action. A C-terminal peripheral modification, introducing a quaternary ammonium salt, is reported and was found to provide a binding pocket-modified vancomycin analog with a second mechanism of action that is independent of d-Ala-d-Ala/d-Ala-d-Lac binding. This modification, which induces cell wall permeability and is complementary to the glycopeptide inhibition of cell wall synthesis, was found to provide improvements in antimicrobial potency (200-fold) against vancomycin-resistant Enterococci (VRE). Furthermore, it is shown that this type of C-terminal modification may be combined with a second peripheral (4-chlorobiphenyl)methyl (CBP) addition to the vancomycin disaccharide to provide even more potent antimicrobial agents [VRE minimum inhibitory concentration (MIC) = 0.01–0.005 μg/mL] with activity that can be attributed to three independent and synergistic mechanisms of action, only one of which requires d-Ala-d-Ala/d-Ala-d-Lac binding. Finally, it is shown that such peripherally and binding pocket-modified vancomycin analogs display little propensity for acquired resistance by VRE and that their durability against such challenges as well as their antimicrobial potency follow now predictable trends (three > two > one mechanisms of action). Such antibiotics are expected to display durable antimicrobial activity not prone to rapidly acquired clinical resistance.